2016
DOI: 10.1021/acs.chemmater.6b01394
|View full text |Cite
|
Sign up to set email alerts
|

Self-Supporting Hierarchical Porous PtAg Alloy Nanotubular Aerogels as Highly Active and Durable Electrocatalysts

Abstract: Developing electrocatalysts with low cost, high activity, and good durability is urgently demanded for the wide commercialization of fuel cells. By taking advantage of nanostructure engineering, we fabricated PtAg nanotubular aerogels (NTAGs) with high electrocatalytic activity and good durability via a simple galvanic replacement reaction between the in situ spontaneously gelated Ag hydrogel and the Pt precursor. The PtAg NTAGs have hierarchical porous network features with primary networks and pores from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 50 publications
0
94
0
Order By: Relevance
“…As illustrated in Figure 8 a,b, by partially substituting silver in an as‐obtained Ag hydrogel with platinum by a post GRR, a hierarchically structured Pt–Ag nanotubular gel was obtained . It was found that the original building blocks, e.g., fused Ag NWs, were converted to interconnected nanotubes with a similar diameter (several tens of nanometers), which were made up of many thin NWs (diameter of ≈2.6 nm).…”
Section: Fabrication Strategiesmentioning
confidence: 99%
“…As illustrated in Figure 8 a,b, by partially substituting silver in an as‐obtained Ag hydrogel with platinum by a post GRR, a hierarchically structured Pt–Ag nanotubular gel was obtained . It was found that the original building blocks, e.g., fused Ag NWs, were converted to interconnected nanotubes with a similar diameter (several tens of nanometers), which were made up of many thin NWs (diameter of ≈2.6 nm).…”
Section: Fabrication Strategiesmentioning
confidence: 99%
“…The metallic aerogels consisting of different metals have their unique properties. Pt‐based aerogels are versatile electrochemical catalysts, showing excellent catalytic activity in numerous reactions, such as oxygen reduction reaction, and formic acid and alcohol oxidation . Pd‐based aerogels show excellent catalytic performance in the oxidation of alcohol and formic acid .…”
Section: Preparation and Classification Of Aerogelsmentioning
confidence: 99%
“…[25,26,[38][39][40] Linking aerogel research and nanotechnology, hierarchical aerogels with primary and secondary pore structures, built from shapeengineered NPs, have also been reported in the form of either hollow shell or dendritic particles. [41][42][43] As illustrated in Figure 1, the general synthesis of noble metal aerogels via the sol-gel process consists of three steps: i) the synthesis of nano-sized building blocks (NBBs); ii) the gelation of the NBBs into hydrogels (plus shape-control of the hydrogel) and iii) the supercritical drying of the hydrogel to yield an aerogel. These three strategies are outlined in different colors in paths I (B1-H1-A1), II (B1-H1-H2-A2) and III (B1-B2-H3-A3) of Figure 1.…”
Section: Synthesis and Featuresmentioning
confidence: 99%
“…[44] The relatively weak coordination interaction between the stabilizer and metal NPs is critical for the gelation step (from B1 to H1 in Figure 1), which can be realized via an spontaneous gelation process [25,26,38] or via controlled destabilizations (by heating [45] or adding salt [46] and cross-linkers [47] Besides the porous and interconnected 3D network structure, hierarchical aerogels also possess backbones with locally modified morphologies instead of solid nanochains. As shown in Figure 1, this sub-structure can be obtained either by tailoring the hydrogel via strategy II (B1-H1-H2-A2) [43] or engineering the NBBs via strategy III (B1-B2-H3-A3). [41] At present, the research on metallic hierarchical aerogels prepared by manipulation of the NBBs is still in its infancy and lags far behind the abundance of colloidal metallic nanoarchitectures.…”
Section: Synthesis and Featuresmentioning
confidence: 99%
See 1 more Smart Citation